Esketamine prevents carboprost-induced adverse reactions during cesarean section under combined spinal-epidural anesthesia: a double-blind, randomized trial - Feng Zhou; Qingling Ma; Fanqing Meng; Han Bao; Wei Liu; Guangfen Zhang; Yue Tian (BMC Anesthesiology)
Abstract Objectives To investigate adverse reactions to carboprost reduced by intravenous esketamine administered after childbirth via cesarean delivery with the patient under combined spinal-epidural anesthesia. Methods The study enrolled pregnant women aged 20–40 years, with American Society of Anesthesiologists (ASA) class II or III, and a gestational age of 37 weeks or more. These women had a scheduled cesarean section procedure with the administration of combined spinal-epidural anesthesia. Patients were randomized to receive esketamine 0.5 mg/kg (Group E) or volume-matched normal saline (Group C) immediately after fetal delivery, prior to carboprost administration (250 µg intramuscularly). The primary outcome was the incidence of vomiting during surgery. The secondary outcomes were the incidence of adverse reactions (nausea, chest rigidity, flushed face, tachycardia, cough, shivering), vital signs (HR, RR, MAP, SPO2) and postoperative pain assessed using a Visual Analogue Scale (VAS). Results Eighty-one pregnant women completed the study. The incidence of vomiting (22.5% vs. 56.1%, p < 0.001) and the incidence of nausea, chest rigidity, flushed face, and hypertension were significantly lower in group E than in group C (all p < 0.01), but the incidence of tachycardia was higher in group E (45% vs. 19.5%, p < 0.001). Furthermore, the patients’ arterial partial pressure of oxygen was significantly higher in group E than in group C (91.90 ± 5.14 vs. 79.76 ± 3.96, p < 0.001). Postoperative pain at the incision site, as assessed by Visual Analogue Scale (VAS) score, was significantly reduced at 6 h in the Esketamine group compared to the control group. However, there was no significant difference in uterine contraction pain between the two groups at any time point. Conclusion For women undergoing cesarean delivery under combined spinal-epidural anesthesia, intravenous esketamine administered after delivery of the fetus and prior to carboprost administration during cesarean section under combined spinal - epidural anesthesia was associated with a reduction in the incidence of carboprost - induced adverse reactions and a decrease in postoperative incision pain at 6 h. However, it did not significantly affect postoperative uterine contraction pain. Trial registration Chinese Clinical Trial Registry (Registration number# ChiCTR2100054985); Date of Registration: 30/12/2021.